2023
DOI: 10.3390/polym15030713
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Absorption Behavior of 3D-Printed Polymeric Octet-Truss Lattice Structures of Varying Strut Length and Radius

Abstract: We investigate the compressive energy absorption performance of polymeric octet-truss lattice structures that are 3D printed using high-resolution stereolithography. These structures are potential candidates for personal protective equipment, structural, and automotive applications. Two polymeric resins (high-strength/low-ductility and moderate-strength/high-ductility) were used in this work, and a comprehensive uniaxial tensile characterization was conducted to establish an optimal UV curing time. The externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Increasing the relative density is also advisable, since stress peaks are less likely to occur and are less significant in thinner regions, and the yield force also increases [ 28 ]. The above-mentioned results on the number of cells and relative density are also supported in more recent studies [ 29 ]. It is also possible to achieve better mechanical properties by varying not only the size but also the aspect ratio of the elementary cells [ 30 ].…”
Section: Introductionsupporting
confidence: 80%
“…Increasing the relative density is also advisable, since stress peaks are less likely to occur and are less significant in thinner regions, and the yield force also increases [ 28 ]. The above-mentioned results on the number of cells and relative density are also supported in more recent studies [ 29 ]. It is also possible to achieve better mechanical properties by varying not only the size but also the aspect ratio of the elementary cells [ 30 ].…”
Section: Introductionsupporting
confidence: 80%
“…The stress-strain curves of OT for the 10, 30 and 50% densities represent the stress drop after the onset of plasticity points of approximately 45, 237, and 331 MPa, respectively. In general, the OT, stretch-dominant structures, show oscillation during plastic deformation in compression load [23,24]. In this study, the stress shows an oscillation curve at plateau stress because it corresponds to the partial fracture of the struts.…”
Section: Compression Behavior Of Single-lattice Structuresmentioning
confidence: 64%
“…Jordi et al 34 outlined how various stress levels and strain-rate regimens are affected by printing orientation. Bolan et al 35 demonstrated the energy absorption response of SLA-printed polymeric octet-truss samples with angled alignment.…”
Section: Introductionmentioning
confidence: 99%